Astrocyte deletion of α2-Na/K ATPase triggers episodic motor paralysis in mice via a metabolic pathway - Sarah E. Smith (Nature Portfolio, 2020)
Mutations of α2-Na/K ATPase can cause familial hemiplegic migraine via unclear mechanisms. Here, the authors show that deletion of α2-Na/K ATPase in astrocytes results in gene expression and metabolic changes leading to cortical spreading depression and episodic transient motor paralysis in mice.